Managerial orientation toward ESG in the pre-acquisition phase of M&A: A multi-regional perspective - Callarelli, Tommaso (My University, 2026)
Nowadays Environmental, Social, and Governance (ESG) criteria have become an important topic in corporate strategy and investment assessment. However, the studies that examine how ESG criteria is processed by managers during the pre-acquisition phase of M&A are limited. The existing literature analysed this topic mainly through quantitative methods, single-country set- tings, and with a focus on post-acquisition phase. As a result of that, it remains less explored the cognitive and interpretative processes through which manager assess ESG criteria during the pre-acquisition stage, and how these processes vary across regions. The thesis addresses these gaps through a qualitative single case study, and the primary data are collected through three semi-structured interviews with managers of a multinational chem- ical group operating in Europe, the Americas, and Asia: the Group Head of Sustainability Strategy and Internal Audit; the Executive Vice President for the Americas; the Executive Vice President for Eurasia. The conceptual framework combines five complementary theoretical perspectives: information asymmetry, behavioural decision theory, institutional theory, stakeholder theory, and upper echelons theory. The interview material was analysed through thematic analysis di- vided in blocks, combining initial codes with themes emerged from the interviewees’ state- ments. The findings reveal that ESG is not interpreted as a uniform organisational construct; within the group, the three distinct managerial orientation coexist, and each one is shaped by the man- ager’s functional role: ESG is considered as a strategic instrument supporting value creation, as a matter of regulatory compliance, and as a factor that needs to be adapted to the local context. The findings also show that each region presents a distinct configuration of regulatory density and stakeholder pressures, and that the European HQ apply its home-region standards across its regional operations. Overall, the theoretical discussion shows that managerial orientations toward ESG criteria in the pre-acquisition phase are shaped simultaneously by the managers’ functional role and by the region’s institutional structure in which the assessment is run. The study is mainly consistent with the existing literature, and it contributes to adding a nuance to two aspects that received limited attention: the qualitative analysis of the pre-acquisition phase, and the observation of how institutional pressures translate into managerial cognition within a single multiregional firm. These two aspects are modest in scope and related to the specific case examined. The main implication is that the analytical focus should shift from the corporate level to the functional level.
Keywords: ownership steering; corporate acquisitions; enterprises; responsible investing; corporate responsibility; societal responsibility; stakeholder groups; strategic leadership; leadership (activity); organisations (systems); fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business